FORMATION OF INFORMATIONAL COMPETENCE OF STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS IN THE PROCESS OF TEACHING HUMANITIES (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the process of information competence formation for High School Students by learning humanitarian subjects.